Offshore Business Processing Outsourcing by Australian Enterprises to Service Providers Located in India - Penter, Kevan John (Curtin University, 2018)
The primary research question for this PhD was: “What are the key factors that contribute to the success of offshore business process outsourcing (OBPO) by Australian and international organisations to service providers located in India and the Philippines?” A qualitative research design in the positivist paradigm was adopted, involving longitudinal case studies of five client companies. A primary contribution was identification of critical success factors for management of OBPO at the individual company level.